2014
DOI: 10.1177/1557988314543792
|View full text |Cite
|
Sign up to set email alerts
|

Gender Norms and Family Planning Practices Among Men in Western Jamaica

Abstract: The objective of this study was to identify the association between gender norms and family planning practices among men in Western Jamaica. A cross-sectional survey of 549 men aged 19 to 54 years attending or visiting four government-operated hospitals was conducted in 2011. Logistic regression models were used to identify factors associated with taking steps to prevent unwanted pregnancy, intention to have a large family size (three or more children), and fathering children with multiple women. Adjusted odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Gender equitable attitudes are believed to be related to contraceptive use [ 23 , 24 , 46 ]. However, in this study, we found that gender attitudes were seldom associated with membership in clusters based on contraceptive and pregnancy experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender equitable attitudes are believed to be related to contraceptive use [ 23 , 24 , 46 ]. However, in this study, we found that gender attitudes were seldom associated with membership in clusters based on contraceptive and pregnancy experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge and attitudes about contraception and fertility are considered “intermediate outcomes”, influencing contraceptive use and influenced by SBC interventions, in the aforementioned framework [ 29 ]. This framework does not consider gender attitudes and norms, but we include them in this same group of variables because of multiple studies showing their association with patterns of contraceptive use [ 23 , 24 , 46 49 ]. We categorize women as having son preference if they preferred more boys than girls, daughter preference if they preferred more girls than boys, and gender balanced/no preference if they expressed no preference or preferred an equal number of girls and boys.…”
Section: Methodsmentioning
confidence: 99%
“…2,11,12 Although it was stated that gender perceptions of married men may affect family planning methods that have already been or will be used, there is an insufficient number of studies on this subject. 3,9,13,14 Therefore, the present study was conducted to determine the relationship between social gender perception and use of family planning among married men in eastern Turkey.…”
mentioning
confidence: 99%
“…Studies from diverse locations in the Global South suggest that men primarily make family planning decisions -including whether contraception is used, the type, and family size (L. MacDonald et al, 2013;Kabagenyi et al, 2014;Walcott et al, 2014). Men are, however, less likely to assume any responsibility for contraceptive use, as both men and women typically believe that reproductive health, and more specifically contraception, is 'women's business' (Drysdale, 2015;L.…”
Section: Agency Power and Empowermentmentioning
confidence: 99%
“…Studies from diverse locations including Western Jamaica and Brazil have shown that men's family planning practices are directly influenced by inequitable gender norms and masculine behaviours (Pulerwitz & Barker, 2008;Walcott et al, 2014). Men who favoured inequitable gender norms were less likely to actively avoid unplanned pregnancies (Walcott et al, 2014); in contrast support for more equitable norms was associated with higher contraceptive usage (Pulerwitz & Barker, 2008).…”
Section: The Influence Of Gender Norms On Family Planning Practicesmentioning
confidence: 99%